The weariness of the self : diagnosing the history of depression in the contemporary age - Ehrenberg, Alain (McGill-Queen's University Press, 2010)
Depression, once a subfield of neurosis, has become the most diagnosed mental disorder in the world. Why and how has depression become such a topical illness and what does it tell us about changing ideas of the individual and society? Alain Ehrenberg investigates the history of depression and depressive symptoms across twentieth-century psychiatry, showing that identifying depression is far more difficult than a simple diagnostic distinction between normal and pathological sadness - the one constant in the history of depression is its changing definition.